2012
DOI: 10.1158/0008-5472.can-11-4072
|View full text |Cite
|
Sign up to set email alerts
|

Smac Mimetic LBW242 Sensitizes XIAP-Overexpressing Neuroblastoma Cells for TNF-α–Independent Apoptosis

Abstract: Despite intensive treatment regimens, high-risk and late-stage neuroblastoma tends to have a poor survival outcome. Overexpression of the apoptotic regulator, X-linked inhibitor of apoptosis protein (XIAP), has been associated with chemotherapy resistance in several cancers including neuroblastoma. Here, we report preclinical evidence that XIAP offers an effective therapeutic target in neuroblastoma. Human and murine neuroblastoma cells were treated with the Smac mimetic LBW242 alone or in combination with cyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…These results also offer potential for the evaluation of similar therapeutic strategies in other embryonal malignancies. It is notable that the activity of LBW242 in combination with cytotoxic chemotherapy has recently been shown in neuroblastoma-another common embryonal tumor of childhood (29).…”
Section: Discussionmentioning
confidence: 99%
“…These results also offer potential for the evaluation of similar therapeutic strategies in other embryonal malignancies. It is notable that the activity of LBW242 in combination with cytotoxic chemotherapy has recently been shown in neuroblastoma-another common embryonal tumor of childhood (29).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies revealed that the synergistic activity of SMAC mimetics with chemotherapeutics is due to canonical NF-kB activation, TNFα production, and activation of the extrinsic apoptosis pathway [120]. In other studies, the reported synergy between SMAC mimetics and chemotherapeutics is reported as independent of TNFα, but dependent on the antagonism of XIAP [136, 137]. Recent studies have shown that genotoxic agents such as etoposide can activate cell death pathways via proteasome-dependent depletion of IAP proteins to promote the assembly of a cytoplasmic cell death-activating platform, ripoptosome [52, 53].…”
Section: Development Of Combination Therapies With Smac Mimetics For mentioning
confidence: 99%
“…Resistance to glucocorticoid-induced apoptosis is one of the major risk factors for relapse and poor outcome in ALL (39). For childhood neuroblastoma, no clear clinical data is available about XIAP expression and clinical outcome, although XIAP-inhibitors significantly affect tumor growth and death resistance of neuroblastoma in vitro and in vivo (40, 41). …”
Section: Xiap Overexpression In Cancermentioning
confidence: 99%